Comfort fitting wrist keyboard - Mohammad Haziq Mohamad Ikhsan (Nanyang Technological University, 2022)
This project demonstrates a smart textile prototype that can be worn comfortably on the wrists and also functions as a keyboard. This report details the progress of the capacitive sensor system of the prototype as well as the difficulties encountered when using it.